Social Comparison Orientation and Social Adaptation Among Young Chinese Adolescents: The Mediating Role of Academic Self-Concept - Miao, Hualing; Li, Zhenxing; Yang, Yingkai; Guo, Cheng (Frontiers in Psychology, 2018)
This study aimed to investigate the relationship among social comparison orientation, academic self-concept (ASC), and social adaptation. A total of 1,658 Chinese adolescents (48.88% male; aged 14-18 years, Mage = 16.01 ± 0.86 years) voluntarily participated in this study and completed questionnaires. Structural equation modeling (SEM) was performed to test the theory-driven model. The results showed that the relationship between comparison of opinion and social adaptation was mediated by ASC but that ASC did not play a mediating role between comparison of ability and social adaptation. These findings indicated that ASC could be one mechanism explaining the link between adolescents’ social comparison orientation and social adaptation. Furthermore, it is possible to intervene in their social comparison orientation and ASC to improve adolescents’ social adaptation.